Exploring the perspective of Muslim scholars on the roles of nurses’ response to disaster: a qualitative study - Husna, Cut (Mental health, religion & culture, 2021)
Aceh is the centre point of the greatest tsunami in 2004 and located along the pacific "ring of fire" with a high risk of disaster. Nurses are the frontline in providing care for survivors. Since the province is the only special Islamic sharia territory in Indonesia, Muslim scholars play an important role in policy enrichment to educate nurses to be able to incorporate Islamic values in delivery of care. This research aims to explore the Muslim scholars' perspectives on the roles of nurses in response to disasters. A phenomenological study using an in-depth interview with nine Muslim scholars was conducted. The data was evaluated through inductive content analysis. The results identified three themes related to their perspectives: Islamic-based perception on disaster; nursing as devotion to God; and integration of Islamic values into nursing practices. Sincerity, patience, prohibition of despair, endeavour, prayer, and resignation were Islamic values required by nurses coping in a disaster.